2018
DOI: 10.3390/c4030048
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Performances of Au–Pt Nanoparticles on Phosphorous Functionalized Carbon Nanofibers towards HMF Oxidation

Abstract: Herein, we reported the utilization of pre-formed Au–Pt nanoparticles deposited on phosphorus functionalized carbons as effective catalysts for the oxidation of 5-hydroxymethylfurfural (HMF) to furandicarboxylic acid (FDCA). Au–Pt nanoparticles have been prepared by a two-step methodology using polyvinyl alcohol (PVA) as protective agent and a combination of NaBH4 and H2 as reducing agents. Three carbon nanofibers (CNFs) with different graphitization degrees have been functionalized through treatment with an H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 53 publications
(74 reference statements)
0
9
0
Order By: Relevance
“…Danis demonstrated that, among all, SV is the most reactive defect towards the addition of an heteroatoms functional group [64]. Based on the typical functional groups found on the carbon surface after a standard functionalization procedure [26,53,65,66], five different functionalization groups were anchored on the SV, i.e. carboxyl (G_COOH), hydroxyl (G_OH), carbonyl (G_CO) and phosphate (G_PO3H) groups (Figure 5).…”
Section: Dft Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Danis demonstrated that, among all, SV is the most reactive defect towards the addition of an heteroatoms functional group [64]. Based on the typical functional groups found on the carbon surface after a standard functionalization procedure [26,53,65,66], five different functionalization groups were anchored on the SV, i.e. carboxyl (G_COOH), hydroxyl (G_OH), carbonyl (G_CO) and phosphate (G_PO3H) groups (Figure 5).…”
Section: Dft Resultsmentioning
confidence: 99%
“…The electronic structure of these catalysts is also affected improving their activity in reactions such as hydrodeoxygenation [23], electrocatalytic oxygen reduction [24], photocatalytic oxidation [25]. Oxygen as a dopant influences the charge transfer between carbon and metal nanoparticles, in fact, most heteroatoms enhance the electron density of the neighbouring carbon atoms increasing the back-donation from C to the metal atoms [26]. Nitrogen and boron doped C-materials have received an increasing consideration as they directly affect the Fermi level of the solid [27,28], and Pd and Pd alloyed NPs supported on them showed promising activity and durability during FA decomposition reaction [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 presents screening of Au-, Ag-, Pd-based and PdAu heterogeneous catalysts for aqueous liquid phase oxidation of HMF under the reaction conditions reported in previous studies (0.15 M HMF, HMF/metal: 200 mol/mol, 60 • C, 3 bar O 2 , 2 equiv. NaOH, 2 h) [17,18].…”
Section: Catalytic Resultsmentioning
confidence: 99%
“…Supported catalysts based on noble metals (Pd, Pt, Ru or Au) [9][10][11][12][13][14] or their combination (bimetallic systems) [15][16][17][18] have demonstrated high activity and selectivity for HMF oxidation. However, their catalytic activity is strongly sensitive to many factors, such as metal dispersion, preparation method, nature of the support, metal-support interaction, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies focus on the synthesis of FDCA and the routes range from stoichiometric chemical transformations 10 to bio-, 11,12 electro- [13][14][15] or heterogeneous metal catalysts. In the latter case, mostly noble metals like Pd, [16][17][18] Pt, [19][20][21] Au [22][23][24][25] or alloys thereof [26][27][28] show high activity.…”
Section: Introductionmentioning
confidence: 99%